SISTEM INFORMASI INVENTORY OBAT PADA RUMAH SAKIT UMUM DAERAH (RSUD) PADANG - Minarni Minarni; Susanti Susanti (Jurnal Momentum ISSN 1693-752X)
Medicine inventory system in the RSUD Padang currently still manual. The type and quantity of medicine always increase with the flow in and out. Handling data with the manual system has several constraints, among other causes of error in checking medicine stock, data redundancy was happened in every reports and less accurate of recording medicine stock in and out so there is some mistake in recording the final stock. To overcome these problems, the writer has a new system design by utilizing network based information technology. It is designed using PHP programming language and MySQL as database. The result of this research is an application program that can control medicine supply and provides updated stock reports. Application program can also monitor the inventory system so that all the stock of medicines and medicines that go out in the barn can be seen clearly without any mistakes that might disrupt the medicine supply process. Thus, this research can improve the efficiency and effectiveness in medicine inventory at the Padang RSUD Pharmacy.